Controlled synthesis and luminescent properties of assembled spherical YPxV1−xO4:Ln3+ (Ln = Eu, Sm, Dy or Tm) phosphors with high quantum efficiency. Issue 65 (16th July 2015) - An, Zhibin; Xiao, Xiuzhen; Yu, Jun; Mao, Dongsen; Lu, Guanzhong
<x xml:space="preserve">Abstract</x> Controlled morphology and energy transfer in assembled spherical YPxV1−xO4:Ln3+ (Ln = Eu, Sm, Dy or Tm) phosphors with higher luminescent quantum efficiency by the EDTA-assisted hydrothermal method.